Money talks, green walks: Does financial inclusion promote green sustainability in Africa? - Samuel Fiifi Eshun; Evžen Kočenda (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This study explores the dynamic relationship between financial inclusion and green sustainability across 38 African countries. We constructed an environmental pollution index and a financial inclusion index covering the period 2000-2021 to account for the several dimensions within both indicators and employed them in the System GMM approach. We also tested for intra-regional heterogeneity in Africa. Our empirical results show that financial inclusion, while economically beneficial, poses a significant risk of environmental degradation and has a distinctive inverted U-shaped relationship. A direct link between increases in financial inclusion and pollution alters at a turning point, beyond which further increments in financial inclusion enhance green sustainability. The same pattern is observed for aggregate output. The results hold even when we control for a score of macro-level determinants. Our findings indicate the existence of an intra-regional heterogeneity in that Southern and Western African states exhibit a more significant negative impact on environmental pollution than Eastern Africa. These results remain robust for alternative proxies of green sustainability. We offer valuable insights for policymakers to promote sustainability through inclusive financial practices and policies in Sub-Saharan Africa.
Keywords: C23; E44; F64; K32; O55; Q43; 330; Environmental Pollution Index; Financial Inclusion Index; Green Sustainability; Sub-Saharan Africa (SSA); System Generalized Methods of Moments (GMM)